2015
DOI: 10.1016/j.ymgme.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies African-ancestry specific variants for metabolic syndrome

Abstract: The metabolic syndrome (MetS) is a constellation of metabolic disorders that increase the risk of developing several diseases including type 2 diabetes and cardiovascular diseases. Although genome-wide association studies (GWAS) have successfully identified variants associated with individual traits comprising MetS, the genetic basis and pathophysiological mechanisms underlying the clustering of these traits remain unclear. We conducted GWAS of MetS in 1,427 Africans from Ghana and Nigeria followed by replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 86 publications
1
34
0
Order By: Relevance
“…[36, 37] Other variants may be identified in novel loci based on a higher frequency of risk alleles in this population. We used high density imputed genotypes from the 1000 Genomes Project (1000G) to expand the genome coverage of genetic variants so that we could examine the evidence for association with BP traits.…”
Section: Introductionmentioning
confidence: 99%
“…[36, 37] Other variants may be identified in novel loci based on a higher frequency of risk alleles in this population. We used high density imputed genotypes from the 1000 Genomes Project (1000G) to expand the genome coverage of genetic variants so that we could examine the evidence for association with BP traits.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, associations in these genes in EA and AA have been observed to be broadly similar[78, 84, 87, 88]. Both LPL and CETP have been implicated in genome-wide studies of MetSyn in EA [89, 90], AA [91], and, recently, in Africans[92]. …”
Section: Genomic Influences On Interethnic Differences In Serum Lipidsmentioning
confidence: 99%
“…In fact, these factors, modifiers, and traits can be intertwined in such curious ways to account for subtle differences in disease expression among different ethno-cultural populations. For example, Tekoya-Ayele et al (100) found that certain SNPs associated with metabolic syndrome (MetS) risk implicated physiologic pathways involving brain function and insulin resistance, and Simons et al (101) found that financial pressures in patients with low-income levels were associated with epigenetic measures, or "weathering," of biological aging. A common-ality among cardio-metabolic risks is inflammation, and Kocarnik et al (102) found 16 SNP-C-reactive protein (CRP) associations spanning multiple ancestral groups (European American, African American, and Hispanic, but not Asian/Pacific Islander or Native American), with many exhibiting pleiotropic effects.…”
Section: Biological Factors In Diabetes Influenced By Culture -Generamentioning
confidence: 99%